Impact of Formative Feedback on Students’ Problem-Solving Performance in Mathematics: A Study in Secondary Level Students in Dolakha District, Nepal - Dahal, Prem Prasad; Kafle, Bhuban; G.C., Laxmi (Journal of Mathematics Education, 2026)
This study intends to study the relationship of teacher given formative feedback and problem solving performance of the students in mathematics at secondary level in Dolakha District, Nepal. A quantitative cross-sectional survey design was adopted and data was collected from 228 students (Grade ten) who were selected from five secondary schools (three public and two private), a rural - semi-urban district context. A structured questionnaire measuring three constructs Formative Feedback Practices (FFP), Problem Solving Performance (PSP) and Perception of Feedback (POF) using a five point Likert scale was used. Descriptive statistics showed quite high mean scores of FFP (M = 3.98, SD = 0.66), PSP (M = 4.10, SD = 0.55) and POF (M = 3.91, SD = 0.84) with acceptable internal consistency (Cronbach's alpha being in the range of .69 to .75). Pearson product-moment correlation analysis indicated that there were strong and positive relationships between FFP and PSP (r=.80, p